Increased frequency of late‐senescent T cells lacking CD127 in chronic hepatitis C disease. (16th March 2015) - Barathan, Muttiah; Mohamed, Rosmawati; Saeidi, Alireza; Vadivelu, Jamuna; Chang, Li Y.; Gopal, Kaliappan; Ram, Mani R.; Ansari, Abdul W.; Kamarulzaman, Adeeba; Velu, Vijayakumar; Larsson, Marie; Shankar, Esaki M.
Abstract Background Hepatitis C virus (HCV) causes persistent disease in ~85% of infected individuals, where the viral replication appears to be tightly controlled by HCV‐specific CD8+ T cells. Accumulation of senescent T cells during infection results in considerable loss of functional HCV‐specific immune responses. Materials and methods We characterized the distinct T‐cell phenotypes based on the expression of costimulatory molecules CD28 and CD27, senescence markers PD‐1 and CD57, chronic immune activation markers CD38 and HLA‐DR, and survival marker CD127 (IL‐7R) by flow cytometry following activation of T cells using HCV peptides and phytohemagglutinin. Results HCV‐specific CD4+ and CD8+ T cells from chronic HCV (CHC) patients showed increased expression of PD‐1. Furthermore, virus‐specific CD4+ T cells of CHC‐infected subjects displayed relatively increased expression of HLA‐DR and CD38 relative to HCV‐specific CD8+ T cells. The CD4+ and CD8+ T cells from HCV‐infected individuals showed significant increase of late‐differentiated T cells suggestive of immunosenescence. In addition, we found that the plasma viral loads positively correlated with the levels of CD57 and PD‐1 expressed on T cells. Conclusions Chronic HCV infection results in increased turnover of late‐senescent T cells that lack survival potentials, possibly contributing to viral persistence. Our findings challenge the prominence of senescent T‐cell phenotypes in clinical hepatitis C infection.